2014
DOI: 10.1063/1.4890309
|View full text |Cite
|
Sign up to set email alerts
|

Quantum efficiency investigations of type-II InAs/GaSb midwave infrared superlattice photodetectors

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…The material properties, i.e. electronic band structure, of the SL are ruled by the ratio R and it has already been proven that it has an influence on the electrooptical properties of midwave SL photodiodes with the same energy band gap [20] [21]. The objective of this work, therefore, is to explore and investigate the period flexibility of Ga-containing SLs for the LWIR spectral range.…”
Section: I-introductionmentioning
confidence: 99%
“…The material properties, i.e. electronic band structure, of the SL are ruled by the ratio R and it has already been proven that it has an influence on the electrooptical properties of midwave SL photodiodes with the same energy band gap [20] [21]. The objective of this work, therefore, is to explore and investigate the period flexibility of Ga-containing SLs for the LWIR spectral range.…”
Section: I-introductionmentioning
confidence: 99%
“…17,18 For a better understanding of the impact of the GaSb content, we have recently studied the influence of the InAs/ GaSb SL period composition and the thickness on the material and device properties. 19,20 We found that the SL period mainly composed of GaSb (hereto referred to as "GaSbrich") has a higher current density than the SL structure mainly composed of InAs ("InAs-rich") having the same cut-off wavelength of 5 lm at 77 K. The current density difference between these MWIR structures is extremely large with almost a factor of 50.…”
Section: Introductionmentioning
confidence: 81%
“…Fig 6 represents the QE measurement of an InAs-rich nid MWIR FPA (320x256) made in France [2]. The 42% average QE is due to the fact that this structure is double-pass and that the depletion zone is now betterr overlapping with the absorption zone, which allows more hole minority carriers to be collected.…”
Section: Icso 2016 Biarritz France International Conference On Spacementioning
confidence: 99%
“…The fact that increasing the bias voltage also improves the QE means that there is a problem of transport in the InAs-rich structure. Simulations using Hovel equations [2][3] have been performed in order to determine the minority carrier diffusion length. QE is the sum of the contributions of three zones: the quasi neutral zone N (QEn), the depletion zone (QEzce) and the quasi neutral zone P (QEp).…”
Section: A Comparisons Of Several T2sl Structure Designsmentioning
confidence: 99%